Two-dimensional anionic zinc benzenedicarboxylates: Ionothermal syntheses, structures, properties and structural transformation - Weerinradah Tapala (2018)
The ionothermal synthesis of two intercalated two-dimensional zinc benzenedicarboxylates, EMIm 2 [Zn 3 (C 6 H 4 (COO) 2 ) 3 Cl 2 ] (I) and BMIm 2 [Zn 3 (C 6 H 4 (COO) 2 ) 3 Cl 2 ] (II), employing the ionic liquids 1-ethyl-3-methylimidazolium chloride (EMIm-Cl) and 1-butyl-3-methylimidazolium chloride (BMIm-Cl) as solvents, is reported. Detailed characterization by X-ray diffraction, elemental analyses, vibrational and optical spectroscopies, and thermogravimetric analysis is described. The two compounds display an anionic two-dimensional structure with the composition [Zn 3 (C 6 H 4 (COO) 2 ) 3 Cl 2 ] 2- which is intercalated and charge neutralized by the imidazolium cations. The compounds are remarkably stable: neither begins to lose mass until they are heated above 300 C, above which temperature ZnO is obtained. The structural transformation of the anionic layered compounds I and II to a neutral one-dimensional structure with the composition Zn(C 6 H 4 (COO) 2 )(H 2 O) 2 is described. The derived neutral compound shows better thermal robustness. Both the parent and the transformed structures display blue luminescence, arising from ligand centered π → π* and n → π* transitions. © 2013 Elsevier Ltd. All rights reserved.